Therapeutic Effects of Low-Level Laser Therapy (635 nm), Ultrasound, and Combination Therapy on Pain and Function in Patients with Temporomandibular Joint Disorders - Mohammed, Noor Q.; Mahdi, Zainab F.; Abdulhameed, Balsam S. (Journal of Neonatal Surgery, 2025)
Objective: This study aimed to investigate and compare the therapeutic efficacy of low-level laser therapy (LLLT) (635 nm), ultrasound (US), and combination therapy in alleviating pain and improving functional outcomes in patients with temporomandibular joint disorders (TMDs), identifying the most effective modality for managing temporomandibular joint disorder (TMD)-related pain and dysfunction. Methods: A total of 75 Patients diagnosed with TMD were randomly assigned to three treatment groups. Group 1 received laser therapy (635 nm) at 0.3 Watts (W) for 30 seconds per tender point. Group 2 received ultrasound therapy at 0.2 Watts (W) for 30 minutes per application. Group 3 underwent combination therapy (laser 635 nm and ultrasound). Each participant received four treatment sessions (two per week) and was followed up after one month. Clinical assessments included the number of tender sites, mouth opening measured with an electronic digital calliper, and pain intensity recorded using a visual analogue scale. Data was analysed using appropriate statistical methods Results: Patients in the laser therapy group (635 nm) exhibited a statistically significant reduction in pain intensity (P=0.000) at all assessment points, including post-treatment and one-month follow-up. This group demonstrated the most pronounced pain reduction, outperforming the combination and ultrasound groups. Similarly, mouth opening significantly improved in the laser therapy group (P=0.010, P=0.000) at pre-third session, pre-fourth session, and one-month post-treatment, followed by the combination therapy and ultrasound groups. Conclusion: Low-level laser therapy (635 nm) effectively reduces pain and enhances mouth opening in patients with TMD. The findings suggest that LLLT is a promising non-invasive treatment for temporomandibular joint disorder (TMD)-related pain and dysfunction, with combination therapy providing additional benefits. Further research is needed to optimize LLLT protocols and explore long-term outcomes.